2023
DOI: 10.1021/acschembio.2c00878
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Optimal Cell Lines for High-Content Phenotypic Screening

Abstract: High-content microscopy offers a scalable approach to screen against multiple targets in a single pass. Prior work has focused on methods to select “optimal” cellular readouts in microscopy screens. However, methods to select optimal cell line models have garnered much less attention. Here, we provide a roadmap for how to select the cell line or lines that are best suited to identify bioactive compounds and their mechanism of action (MOA). We test our approach on compounds targeting cancer-relevant pathways, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…13B ). We next tested compounds ( 1 - 3 ) against a panel of nine diverse cancer cell lines (Supplementary Table 5 ) using cell painting 40 and high-content imaging to maximize the detection of activity and infer mechanism of action 41 . Phenotypic profiles generated using a customized image analysis pipeline provided in-depth quantification of cell morphology and biomarker staining in comparison with 28 reference compounds across six diverse drug categories with distinguishable phenotypes 42 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…13B ). We next tested compounds ( 1 - 3 ) against a panel of nine diverse cancer cell lines (Supplementary Table 5 ) using cell painting 40 and high-content imaging to maximize the detection of activity and infer mechanism of action 41 . Phenotypic profiles generated using a customized image analysis pipeline provided in-depth quantification of cell morphology and biomarker staining in comparison with 28 reference compounds across six diverse drug categories with distinguishable phenotypes 42 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…12). Furthermore, we found that the real-time capability allowed removal of wells with outlier characteristics before compound treatment, ensuring a reliable and repeatable starting phenotypic state 35 . Such pre-drug assessment is not possible with end-point assays, including high-content imaging which requires cell fixing.…”
Section: Discussionmentioning
confidence: 97%
“…A549 has been shown to be an effective cell model for high-content phenotypic screening 35 . In our work, the A549 clustering analysis revealed interesting insights about MOA of various compounds and their effects on live-cell function.…”
Section: Mechanism Of Action (Moa) Identification Using High-dimensio...mentioning
confidence: 99%
“…21,22 In a recent study, the selection of optimal cell lines for high content screening was investigated because different cell lines can result in different sensitivities to detect different MoAs. 23 In total 3,214 small molecule annotated (i.e. containing information about their putative target and MoA) compounds (including FDA approved drugs) were profiled with Cell Painting on six different cell lines.…”
Section: Discussionmentioning
confidence: 99%